Sustainable tourism from the perspective of local residents :|the case of Büyükada - Görek, Burcu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This paper aims to understand Büyükada residents' approaches and ideas dealing with sustainable tourism on the island. Residents have been divided into three categories: Residents who work in tourism related jobs, residents who work in jobs unrelated to tourism or have been retired and lastly, the authorities. In order to understand their attitudes towards economic, socio-cultural and environmental dimensions of sustainable tourism, a qualitative study has been conducted by employing face-to-face interview method. A total of 23 residents who have been living on the island for at least three years were interviewed. These interviews were analyzed by using content analysis and the results were evaluated by considering the following variables: demographic characteristics, attitudes, values, beliefs, government plans and actions. Considering the results of this study, it can be said that different variables carry different approaches towards sustainability, residents who work in tourism related jobs mostly have concerns about economic sustainability, residents who work in jobs unrelated to tourism or have been retired mostly care about environmental and socio-cultural sustainability and authorities, while having an idea of sustainability like all other residents, lack a definitive approach, therefore are mostly ineffective. Meanwhile, those residents with a higher level of education, who are relatively more affluent and concerned about the future of the Island, have council to tackle the problems and made some successful attempts towards a more sustainable approach.
Keywords: Sustainable tourism -- Turkey -- Büyükada.; Tourism -- Turkey -- Büyükada.